THE EFFECT OF KNOWLEDGE SHARING AND ORGANIZATIONAL CULTURE ON THE PERFORMANCE OF TEACHERS AT STATE SENIOR HIGH SCHOOL 2, SUNGAI PENUH CITY, WITH JOB SATISFACTION AS AN INTERVENING VARIABLE - Fitrina Afrianti; Masrida Zasriati; Osi Hayuni Putri; Wulan Dwi Septina Putri (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2025)
This research aims to determine the influence of knowledge sharing and organizational culture on teacher performance with job satisfaction as an intervening variable.the object of this research is the senior high school 2 sungai penuh.the respondents in this study are teacher at the seniot high school 2 sungai penuh city with a total of 30 people. based on the results of the previous analysis and discussion,the following can be concluded as follows:knowledge sharing,organizational culture has an influence on the large hall of the senior high school 2 Sungai penuh city, because T count>T table (4,16>0,05).job satisfaction influences the performance of teacher at the senior high school 2,Sungai penuh city because T count>T table (0,40>0,05).knowledge sharing influences job satisfaction.this is proven by T count >T table (0,44>0,05).organizational culture has an effect on job satisfaction.this is proven by T count>T table (0.26>0,05) job satisfaction has an effect as an intervening variable between knowledge sharing on the performance of teachers at the senior high school 2,Sungai penuh city.this is proven by T count<T table (0.83>0,05)